The Influence of Organizational Culture, Work Spirit and Job Satisfaction on Employee Work Productivity at the Ministry of Religion Office - Sulaeman, Sulaeman; Mappatompo, Mappatompo; Anggoro KR, Badawi M. Yusuf Alfian Rendra (Journal La Sociale, 2025)
The Influence of Organizational Culture, Work Morale and Job Satisfaction on Employee Work Productivity at the Makassar City Ministry of Religion Office. Supervised by Mr. Andi Mappatompo Badawi as Supervisor I and Mr. M. Yusuf Alfian Rendra Anggoro KR as Supervisor II. This research aims to analyze, test and determine the influence of organizational culture, work enthusiasm and job satisfaction on employee work productivity at the Makassar City Ministry of Religion Office. The type of research used is quantitative research with a sample of 93 respondents using a questionnaire as a source of data collection, the analysis used is multiple linear regression analysis. The research results show that organizational culture has a positive and significant effect on employee work productivity, work morale has a positive but not significant effect on employee work productivity, job satisfaction has a positive and significant effect on employee work productivity.